THE IMPACT OF DEVELOPING A QUALITY CULTURE ON ORGANIZATIONAL COMMITMENT IN ISLAMIC UNIVERSITIES - Alim, Wahab Syakhirul; Solichin, Mohammad Muchlis (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Quality culture is seen as an important part of the higher education system in developing the quality of its management to achieve learning communities in tertiary institutions that carry out educational processes oriented towards achieving quality standards. Purpose: The formulation of the research problem is: 1) How is the development of a quality culture at the Madura State Islamic Institute and Nazhhatut Thullab Islamic High School Sampang Madura? 2) What is the impact of the development of a quality culture on organizational commitment at the Madura State Institute of Islamic Studies and the Islamic College of Nazhatut Thullab Sampang Madura? Merhod: To answer the questions in the problem formulation above, the researcher uses qualitative research with interviews and documentation as a means of collecting data. Data analysis used in this study included data reduction, data presentation and decision making. Result: From the research carried out, the results are as follows: 1) quality development carried out at IAIN Madura and IAI NATA is carried out in aspects, behavior that describes the university's motto (vision), internal and external input is accommodated as a basis for decision making, employee involvement, education and training, reward system, 2) the development of a quality culture in the two tertiary institutions above has an impact on the commitment of lecturers and staff to survive, have a career, be proud and be happy in the two tertiary institutions.